M-cholinolytics and prescription of therapy in urge syndrome - V V Danilov; S A Luchinsky; V V Danilov; I Yu Volnych; V V Danilov (IP Berlin A.V., 2013)
The analysis of 220 cases of long-term management of patients with overactive bladder syndrome which took M-cholinolytics showed that some patients had pain syndrome above the inguinal region (approximately 8%) which was resolved after drug withdrawal. Based on neurophysiological model, the original hypothesis of such adverse effects was presented which was based on double effects of autonomic agent - detrusor and concomitantly vascular tone of pelvic organs. The comparison of various drug products from group of M-cholinolytics showed that tertiary amines significantly more frequently resulted in such adverse effect than trospium chloride related to quaternary amines. As far the developed model was concerned, the phenomenon was explained by mode of action of antimuscarinic agents